Dexamethasone impacts zinc levels in goats by regulating zinc transportation in the colon and the metabolism in the liver. (25th June 2018) - Hua, Canfeng; Geng, Yali; Chen, Qu; Niu, Liqiong; Cai, Liuping; Tao, Shiyu; Ni, Yingdong; Zhao, Ruqian
Abstract: The aim of this study was to investigate the effects of dexamethasone (DEX) on zinc metabolism in goats. In this study, 10 goats were randomly divided into two groups. One group was injected with dexamethasone (Dex group) and the other group was injected with saline (Con group). Dex treatment significantly decreased hepatic zinc levels ( p  <   .01) and increased Zn transporters 1 (ZNT‐1) expression ( p  <   .05). The concentration of zinc in the cecal and colonic contents was significantly increased ( p  <   .05). However, zinc levels were increased only in the colon tissues ( p  <   .05) but not in the cecal tissues ( p  >   .05). A dramatic increase in Zrt‐, Irt‐related proteins 14 (ZIP‐14) expression ( p  <   .05) following Dex treatment was also observed and likely induced the elevated zinc levels in the colon, and a significant reduction in Zip‐14 methylation ( p  <   .05) may be responsible for the observed increase in Zip‐14 expression. Together, these results indicate that Dex influences zinc homeostasis by increasing hepatic ZNT‐1 and colonic ZIP‐14 expression. Additionally, these results provide valuable information for the clinical application of Dex.